The Role of Perceived Organizational Support, Organizational Culture, and Servant Leadership in The Contextual Performance of The Startup Employees - Aulia Aulia; Ciptasari Prabawanti; Zaenal Wafa (Universitas Ahmad Dahlan, 2022)
A functional performance assessment is crucial for planning an employee's career development working in the company. Nevertheless, related to the performance, so far, conceptually, it is divided into two, e.g., task and contextual performance. Subsequently, directly or indirectly, contextual performance influences individual task performance. Therefore, the study related to particular contextual performance becomes an essential matter to discuss. This study related to contextual performance is relatively scarce; moreover, it does not even find primarily in startup companies. The research objective is to observe the role of perceived organizational support, organizational culture, and servant leadership on contextual performance. The method in this study is quantitative correlation research. The participants in this research are startup employees who are actively working. The instrument for collecting data is a psychological scale consisting of a contextual performance scale, perceived organizational support scale, organizational culture scale, and servant leadership scale. The data analysis technique employs multiple regression analysis. The research result indicates that the coefficient values are R=0.589, F=4.615, and p=0.01 (p<0,05). Based on the data analysis result, simultaneously, perceived organizational support, organizational culture, and servant leadership is indeed contributed to contextual performance.Keywords: Organizational culture, Contextual performance, Perceived organizational support, servant leadership, Startup